2000
DOI: 10.1090/conm/258/1778113
|View full text |Cite
|
Sign up to set email alerts
|

On the universal space for group actions with compact isotropy

Abstract: Let G be a locally compact topological group and EG its universal space for the family of compact subgroups. We give criteria for this space to be G-homotopy equivalent to a d-dimensional G-CW -complex, a finite G-CW -complex or a G-CW -complex of finite type. Essentially we reduce these questions to discrete groups, and to the homological algebra of the orbit category of discrete groups with respect to certain families of subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 17 publications
(17 reference statements)
1
37
0
Order By: Relevance
“…Throughout this section, let G be a discrete group and let F be the family of finite subgroups of G. Recall that the geometric dimension for proper actions gd(G) of G is by definition the smallest possible dimension that a model for EG can have and note that if X is a model for EG, then the cellular chain complexes [30]). This implies that cd(G) gd(G).…”
Section: Geometric Versus Cohomological Dimensionmentioning
confidence: 99%
“…Throughout this section, let G be a discrete group and let F be the family of finite subgroups of G. Recall that the geometric dimension for proper actions gd(G) of G is by definition the smallest possible dimension that a model for EG can have and note that if X is a model for EG, then the cellular chain complexes [30]). This implies that cd(G) gd(G).…”
Section: Geometric Versus Cohomological Dimensionmentioning
confidence: 99%
“…If G is a discrete subgroup of a Lie group L with finitely many path components, then for any maximal compact subgroup K ⊆ L, the space L/K with its left G-action is a model for EG. More information about EG can be found in [14,27,51,58,62].…”
Section: Novikovmentioning
confidence: 99%
“…There is an algebraic dimension cdG that bears a close relationship to gdG, analogous to the relationship between cohomological dimension and the minimal dimension of an Eilenberg-Mac Lane space. It can be shown that cdG = gdG except that there may exist G for which cdG = 2 and gdG = 3, and cdG is an upper bound for the cohomological dimension of any torsion-free subgroup of G [23]. In view of this we may split the strong form of Brown's question into two parts, one geometric and one algebraic.…”
Section: Introductionmentioning
confidence: 99%